2018
DOI: 10.11622/smedj.2017042
|View full text |Cite
|
Sign up to set email alerts
|

Eating psychopathology and psychosocial impairment in patients treated at a Singapore eating disorders treatment programme

Abstract: INTRODUCTIONThere is limited data on the psychopathology of eating disorders in Singapore. This study: (a) described levels of eating psychopathology and psychosocial impairment among individuals diagnosed with eating disorders at our hospital; and (b) compared the related psychopathology of these patients. RESULTS A majority of participants were women and of Chinese ethnicity. Diagnoses included anorexia nervosa (AN; 41.6%), bulimia nervosa (BN; 29.6%) and eating disorder not otherwise specified (EDNOS; 28.8%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 33 publications
0
10
2
Order By: Relevance
“…In contrast to past research conducted in other Asian countries (Lee, Ho, & Hsu, 1993), the general clinical presentation of EDs in Singapore appears to be similar to that of Western cultures (Ng et al, 2018;Teh et al, 2020;Ung, Lee, & Kua, 1997). Patients with EDs reported the presence of body image disturbance, high weight and shape concerns and frequent engagement in compensatory behaviors.…”
contrasting
confidence: 85%
See 2 more Smart Citations
“…In contrast to past research conducted in other Asian countries (Lee, Ho, & Hsu, 1993), the general clinical presentation of EDs in Singapore appears to be similar to that of Western cultures (Ng et al, 2018;Teh et al, 2020;Ung, Lee, & Kua, 1997). Patients with EDs reported the presence of body image disturbance, high weight and shape concerns and frequent engagement in compensatory behaviors.…”
contrasting
confidence: 85%
“…Due to the lack of Singapore data, the IHME estimates are extrapolated from prevalence in other Asian countries. Studies that gather data on EDs in Singapore are primarily based on the national treatment centers for EDs (Goh, Lee, Lim, & Lum, 2016; Lee, Lee, Pathy, & Chan, 2005; Ng, Kuek, & Lee, 2018). Between 1994 and 2002, 138 patients (91.3% females) with AN presented for treatment at a tertiary hospital (Lee et al, 2005); between 2003 and 2010, 281 patients (95.7% females, ages 12–40 years with a BMI < 18.5 kg/m 2 presented with AN (55.2% with AN‐restrictive subtype, 24.9% with AN‐binge/purge) and eating disorder not otherwise specified (EDNOS; 19.9%; Goh et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies (n = 644) used a clinical interview plus an additional research assessment with an adapted version of the eating disorder diagnostic scale (Stice, Telch, & Rizvi, 2000) to confirm onset date (Brown et al, 2018;Flynn et al, 2020). Two studies (n = 2,027) measured onset date using participant self-report (Beat, 2017;Schlegl et al, 2019), one (n = 285) reported that this was 'assessed at admission' (Bühren et al, 2013), three (n = 1,298) relied on young person and/or parental self-report (Kwok et al, 2019;Lieberman et al, 2019;Shu et al, 2015), and three (n = 503) did not define how onset was determined (Andrés-Pepiñá et al, 2019;Ng et al, 2018;Nicholls et al, 2011). To measure the start of treatment, or end of DUED, six studies (n = 1,508) used the date of entrance into specialised treatment (Andrés-Pepiñá et al, 2019;Brown et al, 2018;Bühren et al, 2013;Flynn et al, 2020;Kwok et al, 2019;Lieberman et al, 2019), five (n = 2,433) used questionnaires (Beat, 2017;Neubaeur et al, 2014;Nicholls et al, 2011;Schlegl et al, 2019;Weigel et al, 2014), and three (n = 1,091) did not explicitly define how start of treatment date was measured (Gumz et al, 2018;Ng et al, 2018;Shu et al, 2015).…”
Section: Methodological Characteristics and Qualitymentioning
confidence: 99%
“…The CIA has been the most widely used questionnaire to measure the severity of psychosocial impairment due to eating disorders [4]. Overseas it has been translated into various languages and, with the reliability and validity of these translated versions having already been confirmed, they are widely used for research and clinical use [5][6][7][8][9][10][11]. In order to investigate if the CIA can be used for patients with different cultural, socioeconomic, and ethnic backgrounds, versions were developed for non-Western populations such as Fijian [6], Persian [9], and Singaporean (the majority of participants of Chinese ethnicity) [11].…”
Section: Introductionmentioning
confidence: 99%